(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article discusses the numerous advantages of learning a foreign language, specifically focusing on the English language. It explores how acquiring proficiency in English can positively influence intercultural relationships by fostering better communication and mutual understanding among people from diverse cultural backgrounds. Additionally, the article highlights the crucial role English plays in today’s globalized society, where it serves as a bridge for international collaboration in fields such as business, education, science, and technology. Mastering English not only enhances career opportunities but also empowers individuals to engage in a more interconnected world, promoting cultural exchange and global cooperation.